2015
DOI: 10.1021/acs.analchem.5b02254
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics in Doping Control: Detection of New Markers of Testosterone Misuse by Ultrahigh Performance Liquid Chromatography Coupled to High-Resolution Mass Spectrometry

Abstract: ABSTRACT:The use of untargeted metabolomics for the discovery of markers is a promising and virtually unexplored tool in the doping control field. Hybrid quadrupole time-of-flight (QTOF) and hybrid quadrupole Orbitrap (Q Exactive) mass spectrometers, coupled to ultra-high pressure liquid chromatography are excellent tools for this purpose. In the present work, QTOF and Q Exactive have been used to look for markers for testosterone cypionate misuse by means of untargeted metabolomics. Two different groups of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 31 publications
1
44
0
1
Order By: Relevance
“…The use of the LC-MS/MS allows for the direct analysis of intact phase II metabolites [17][18][19], avoiding the time consuming and laborious steps of enzymatic hydrolysis and derivatization needed for the GC-MS analysis. Additionally, the coupling of LC with versatile and sensitive MS analyzers allowed for the reevaluation of the T metabolome [20][21][22] and led to the identification of many unreported metabolites of endogenous steroids [20,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the LC-MS/MS allows for the direct analysis of intact phase II metabolites [17][18][19], avoiding the time consuming and laborious steps of enzymatic hydrolysis and derivatization needed for the GC-MS analysis. Additionally, the coupling of LC with versatile and sensitive MS analyzers allowed for the reevaluation of the T metabolome [20][21][22] and led to the identification of many unreported metabolites of endogenous steroids [20,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1‐CPG was synthesized and purified as previously described . The β‐glucuronidase preparation (from Escherichia coli type K12) was purchased from Roche Diagnostics (Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, several T metabolites conjugated with either cysteine or with glucuronic acid but resistant to enzymatic hydrolysis have demonstrated their suitability for the detection of the oral administration of testosterone. Additionally, in a previous study conducted by our laboratory, an untargeted metabolomics analysis revealed the presence of a novel marker for the determination of T cypionate administration. The structure of this marker was confirmed to be 1‐cyclopentenoylglycine (1‐CPG), that likely originates from the metabolism of cypionic acid released after hydrolysis of the administered T ester .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, knowing the limits of targeted approach [21] and the confirmed potential of untargeted approach [22], the present study aimed to assess the global biological effect of stanozolol-treatment by means of chemometric models, after generating and comparing horse urine LC-HRMS fingerprints collected from control and stanozololtreated horses. Furthermore, by the means of metabolomics approach, the possibility to extend the detection window of stanozolol is considered.…”
Section: Generic Namementioning
confidence: 99%